Motivasi Partisipasi Ibu Rumah Tangga Perumahan Papanmas Kabupaten Bekasi terhadap Kegiatan Pengajian Majlis Ta’lim Ar-Ridwan - Yunisa Ratna Dewi; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (FONDATIA, 2022)
The ta’lim Ar-Ridwan assembly is the community’s gathering forum for religious presentations in the Papanmas Bekasi housing. The ta’lim assembly called for the public to instill akhlakul karimah and establish amar ma’ruf nahi munkar. The methods used in this study are descriptive qualitative, data collection done with observation and interview. Sources interviewed were the chairman of ta’lim Ar-Ridwan’s house and some members of the jama’ah council of ta’lim. As for data analysis in this study is the reduction of data, the presentation of data and drawing conclucions. The study has concluded that the motivation for the mothers’ participation of the house of Papanmas Bekasi to the ta’lim Ar-Ridwan distribution activities consists of both instrinsic motivation and extrinsik motivation. Intrinsic motivation is to seek religious science, to enhance the quality of worship and tighten the silaturahmi ropes. But extrinsik motivation is due to the influence of friends and the dues of the majelis ta’lim that are used for religious and social activities. Supporting the motivation for the Papanmas Bekasi housing activities of the majelis ta’lim Ar-Ridwan is an adequate means and infranstructure, an awareness of studies, and interesting methods and lecture materials. As for the slowing factor, the destruction of tools and infrastructure and unsupportive weather.